PEMAKNAAN TINGKAT PERTAMA (DENOTATIF) CERITA RAKYAT DONGKREK DI KABUPATEN MADIUN - Affandi, Ainur Rofiq (JURNAL PESONA, 2018)
AbstractDongkrek Art is art that are a typical village communities Mejayan identity, Madiun district. As a unique identity, there is meaning in the arts dongkrek conveyed through the symbols of the form of the roles played by the player. So far the story raykyat dongkrek as a sacred rituals by village communities Mejayan. Through the roles played by players appear various meanings and new symbols of folk stories dongkrek. Therefore, the focus in this research is about the meaning and symbols found in the story of the people Dongkrek in Madiun. This research uses qualitative approach etnografis namely examine business a certain cultural groups in data processing, since reduce, presents and verify and concluded data, do not use the calculations mathematically dans tatistik, but more emphasis on the interpretive studies.Key words: folk stories Dongkrek, meaning symbol.